2012
DOI: 10.1159/000335620
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise Training on Red Blood Cell Production: Implications for Anemia

Abstract: Exercise training can increase total Hb and red cell mass, which enhances oxygen-carrying capacity. The possible underlying mechanisms are proposed to come mainly from bone marrow, including stimulated erythropoiesis with hyperplasia of the hematopoietic bone marrow, improvement of the hematopoietic microenvironment induced by exercise training, and hormone- and cytokine-accelerated erythropoiesis. Anemia is one of the most common medical conditions in chronic disease. The effects of exercise training on count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 164 publications
4
66
0
8
Order By: Relevance
“…This could not be ascribed to differential use of iron tablets: excluding the 25 iron tablet users (6 athletes, 19 non athletic normals) the higher ratio of [100*haemoglobin]/SaO 2 in the athletic group persisted (median 16.6 [IQR 14.7, 20.0] vs 15.2 [IQR 12.2, 17.7], p = 0.016). This would be in keeping with the limited evidence suggesting that exercise training can increase total haemoglobin and red cell mass, attributed to stimulated bone marrow erythropoiesis [49].…”
Section: Resultssupporting
confidence: 82%
“…This could not be ascribed to differential use of iron tablets: excluding the 25 iron tablet users (6 athletes, 19 non athletic normals) the higher ratio of [100*haemoglobin]/SaO 2 in the athletic group persisted (median 16.6 [IQR 14.7, 20.0] vs 15.2 [IQR 12.2, 17.7], p = 0.016). This would be in keeping with the limited evidence suggesting that exercise training can increase total haemoglobin and red cell mass, attributed to stimulated bone marrow erythropoiesis [49].…”
Section: Resultssupporting
confidence: 82%
“…1e3 In endurance athletes, sports anemia is thought to be mainly related to hemodilution, which can be defined as the increase in plasma volume exceeding the increase of total red cell mass and causing a reduction in RBC count, Hb, or hematocrit. 3,4 Besides hemodilution, various factors contribute to sports anemia, including exercise-induced oxidative stress, iron deficiency, gastrointestinal bleeding, hematuria, and hemolysis resulting from foot-strike and/or from compression of contracting muscles on capillaries. 1,2,5 In the literature, there are remarkable findings reporting significant changes of Hb, hematocrit, and RBC count in runners who strenuously push themselves during a marathon race, with mean cell volume (MCV) and mean cell Hb (MCH) negligibly affected.…”
Section: Introductionmentioning
confidence: 99%
“…From these studies, it can be speculated that the decrease in cancer risk via greater physical activity may be accomplished by attenuating immune senescence normally occurring with aging (Westerlind 2003). Recently, Hu and Lin (2012) suggested that exercise training can increase total hemoglobin and RBC mass, enhancing oxygen-carrying capacity. They suggested that exercise training improved the hematopoietic microenvironment.…”
Section: Discussionmentioning
confidence: 99%